Do firms pay bonuses to protect jobs? - Balázs Reizer (Hungarian Academy of Sciences, Institute of Economics, 2016)
A large share of workers receives bonus payments besides their base wage. The benefits of flexible wage components in remuneration are twofold: they can incentivize workers and make it easier to adjust wages downward in response to negative shocks. Using data on bonus payments of Hungarian workers from linked employer-employee data, I disentangle the importance of these two factors to assess their respective importance. First, I show that bonus payments flexibly adjust to the revenue shocks of firms. At the same time, the separation rate of workers without bonuses do not react more to revenue changes than the separation rate of workers with bonuses. Bonus paying firms are shown to be financially more stable, larger and more productive, and they have less volatile revenue than firms not paying bonuses. These facts are consistent with a wage posting model with incentive contracting, but they are hard to reconcile with models emphasizing the role of bonus payments in alleviating wage rigidity. These results indicate that wage flexibility regulations may not affect the employment responses of firms to negative shocks.
Keywords: J31; J23; J42; 330; Wage Level and Wage Structure; Labor Demand; Monopsony